UJI RELIABILITAS DAN VALIDITAS UKURAN KEMISKINAN DI INDONESIA - Erry Jayanti; Cut Italina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
The purpose of this study is to examine the validity and reliability of determining poor households based on the size of the approach, as well as to examine the comparative level of poverty in Indonesia based on micro and macro data. In addition to using data on the number of poor people in Indonesia, the data used are sourced from BPS, namely micro and macro poverty indicators based on information from the 2020 Susenas, which consists of eight criteria for poor households on a micro basis and 5 groups of poor households on a macro basis. The classification of data is done by means of cross tabulation, while the data analysis model uses the Kuder-Richardson -20 formula, for reliability testing and uses the Criterion - related validity and validation model to test the validity of poverty data. The results of the data test show that the micro-poverty measure is still partially valid for each bvariable. While the reliability test shows that the measure of micro poverty is at a moderate level of reliability. The poverty variable is not yet specific which shows regional characteristics which makes the research results not one hundred percent valid and in accordance with BPS indicators and the multidimensional meaning of poverty. Keywords : macro poverty, micro poverty, Realibilitas, Validitas